ESTIMASI NILAI PEMULIAAN PEJANTAN KAMBING SABURAI BERDASARKAN BOBOT SAPIH DI KELOMPOK TERNAK MAKMUR II, KECAMATAN GISTING, KABUPATEN TANGGAMUS - Habibi Habibi; Akhmad Dakhlan; Dian Kurniawati; Kusuma Adhianto (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This study aimed to determine the genetic potential of Saburai bucks for weaning weight based on breeding value in the Makmur II Livestock Group, Gisting District, Tanggamus Regency and to determine which individuals deserve to be maintained in the population. This research was conducted in May 2021 at Gisting Atas Village, Gisting District, Tanggamus Regency. This study used a survey method using weaning weight data at first and second parity that has been recorded by farmers in the recording. The observed variables were birth weight, weaning weight, weaning age, age of the dam at the time of giving birth, birth type, and sex of kid. Weaning weight data at each parity were corrected for the age of the dam, sex, and type of birth of kids. Repeatability estimates was calculated using interclass correlation method, while heritability estimates was calculated using paternal halfsib with one way layout. The results of this study showed that the average corrected weaning weight of Saburai goat was 14.35±0.33 kg, heritability value was 0.39±0.20 (high category), repeatability estimate was 0.61 (high category), and the average breeding value of weaning weights of Saburai buck was 13.96 kg. The breeding values of 5 Saburai goats in the Makmur II Livestock Group, Gisting District, Tanggamus Regency, were Os (14.09 kg), Ba (14.02 kg), Pa (13.94 kg), Ad (13.89 kg), Pg (13.86 kg). Keywords: Breeding value, Heritability, Repeatability, Saburai buck, Weaning weight